2017
DOI: 10.1016/j.jff.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Study on the digestion of milk with prebiotic carbohydrates in a simulated gastrointestinal model

Abstract: This is a repository copy of Study on the digestion of milk with prebiotic carbohydrates in a simulated gastrointestinal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…However, there are some in vivo studies performed with neonatal and growing rats showing that GOS are selectively digested in the small intestine 7,8 , challenging the assumption that GOS reach the colon with their original structure fully intact. Similar findings have been recently reported with in vitro digestion models using a rat small intestinal extract 9,10 .…”
Section: Introductionsupporting
confidence: 91%
“…However, there are some in vivo studies performed with neonatal and growing rats showing that GOS are selectively digested in the small intestine 7,8 , challenging the assumption that GOS reach the colon with their original structure fully intact. Similar findings have been recently reported with in vitro digestion models using a rat small intestinal extract 9,10 .…”
Section: Introductionsupporting
confidence: 91%
“…Similar behaviour was obtained in a previous work comparing the digestibility of prebiotics added to milk in an in vitro study with a rat extract. 20…”
Section: Tables 2 and 3 Show The Quantitative Determination Of Indivimentioning
confidence: 99%
“…17,18,19 Recently, the use of mammalian intestinal enzymes has been reported as an excellent alternative method to determine carbohydrate digestion. 20,21,22 In vivo and in vitro studies have reported considerable digestion rates in the small intestine of different types of GOS in rats 20,23,14,24,25 questioning the general acceptance that these compounds reach intact the colon. These authors also have reported a different resistance to the upper gastrointestinal tract conditions as well as a different effect on microbiota depending on the main β-linkage in the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recently, a promising in vitro digestibility method of dietary carbohydrates using rat small intestinal extract (RSIE) has questioned the belief that recognized prebiotics oligosaccharides derived from lactose (GOS) and fructooligosaccharides (FOS) reach the distal portions of colon without alterations. [14][15][16] Therefore, with the aim of gain more insight on the benefits of non-digestible carbohydrates, in this work the digestibility of commercial functional fiber, such as α-galactooligosaccharides derived from peas and different types of fructans have been tested using a rat small intestine extract.…”
Section: Introductionmentioning
confidence: 99%